Humoral and cellular immune response to mRNA SARS-CoV-2 BNT162b2 vaccine in adolescents with rheumatic diseases - Clara Udaondo; Carmen Cámara; Laura Miguel Berenguel; Rosa Alcobendas Rueda; Celia Muñoz Gómez; Claudia Millán Longo; Blanca Díaz - Delgado; Iker Falces-Romero; Mariana Díaz Almirón; Jordi Ochando; Ana Méndez - Echevarría; Agustín Remesal Camba; et al. (BMC, 2022)
Abstract Background Data about safety and efficacy of the mRNA SARS-CoV-2 vaccine in adolescents with rheumatic diseases (RD) is scarce and whether these patients generate a sufficient immune response to the vaccine remains an outstanding question. Objective To evaluate safety and humoral and cellular immunity of the BNT162b2 vaccine in adolescents 12 to 18 years with RD and immunosuppressive treatment compared with a healthy control group. Methods Adolescents from 12 to 18 years with RD followed at Hospital La Paz in Madrid (n = 40) receiving the BNT162b2 mRNA vaccination were assessed 3 weeks after complete vaccination. Healthy adolescents served as controls (n = 24). Humoral response was measured by IgG antiSpike antibodies, and cellular response by the quantity of IFN-γ and IL-2 present in whole blood stimulated with SARS-CoV-2 Spike and M proteins. Results There were no differences in spike-specific humoral or cellular response between groups (median IFN-γ response to S specific protein; 528.80 pg/ml in controls vs. 398.44 in RD patients, p 0.78, and median IL-2 response in controls: 635.68 pg/ml vs. 497.30 in RD patients, p 0.22. The most frequent diagnosis was juvenile idiopathic arthritis (26/40, 65%) followed by Lupus (6/40, 15%). 60% of cases (23/40) received TNF inhibitors and 35% (14/40) methotrexate. 40% of patients (26/64) had previous SARS-CoV-2 infection, 9 in the control group and 17 in the RD patients without differences. Of note, 70% of infections were asymptomatic. A higher IFN-γ production was found in COVID-19 recovered individuals than in naive subjects in both groups (controls: median 859 pg/ml in recovered patients vs. 450 in naïve p 0.017, and RD patients: 850 in recovered vs. 278 in naïve p 0.024). No serious adverse events or flares were reported following vaccination. Conclusions We conclude that standard of care treatment for adolescents with RD including TNF inhibitors and methotrexate did not affect the humoral and the cellular immunity to BNT162b2 mRNA vaccination compared to a healthy control group. The previous contact with SARS-CoV-2 was the most relevant factor in the immune response.